The Croatian Sense of Identity among the Immigrants of Magallanes (Chile) and Their Descendants during the Final Period of the Yugoslav Monarchy (1939–1945) - Mateo Martinić (Migracijske i etničke teme, 2002)
The article reviews political events which occurred in former Yugoslavia during the final period of the monarchy (1939–1945), from the perspective of Croatian emigrants in Magallanes (Chile) and their descendants. In that period there were two lines of thought. One, apparently more widely held, was decidedly pro-Yugoslav and, as such, accepted the hegemony of Greater Serbia. The other, conspicuously in the minority, emphasized its Croatian identity and identified with those who, in the distant homeland, were struggling for a statute of autonomy, and for full recognition of their historical and cultural individuality. From their respective points of view, each group analyzed the news which arrived from Europe, especially those following the defeat and occupation of Yugoslavia by the German forces (1941) and the subsequent creation of the Independent Croatian State. From then onward, the article presents and assesses the corresponding demonstrations of opinion which, following the evolution of events showed the predominance of the pro-Yugoslavs and, within that tendency, the supporters of the partisan leader Tito. Explicitly or tacitly, the Chilean-Croatian community of Magallanes was notably pro-Yugoslav for the next half-century. Nonetheless, the determined spirit of Croatian patriotism was kept alive by a few, bursting forth with renewed vigour when Croatia obtained its independence in 1991.